The Association between Neutrophil Lymphocyte Ratio and Obesity in Children - M. Alaa, Dina; S. Zeid, Mayada; El-Ashry, Rasha A.; M Mosaad, Youssef; Elsharkawy, Ashraf A. (Journal of Neonatal Surgery, 2025)
Background: Obesity is a multifactorial disease and has been considered as a global problem owing to the increase in its prevalence all over the world in adult subjects as well as in pediatric population, as it is expected that more than 50 per cent of the global population could be obese by 2030 (Abdelmajed et al., 2017). Overweight is considered a common problem in Egypt, and as per the WHO statistics the measured prevalence of overweight is sixty one–seventy per cent of the whole population aged twenty and more, with percentage sixty five per cent of males and seventy six per cent of females aged fifteen and more (Abdelmajed et al., 2017). Overweight was determined among 19.5 per cent of the children in an Egyptian study (Hassan et al., 2016). Aim: The aim of this work is to detect the role of inflammation in the development of IR and overweight, by studying the association between neutrophil lymphocyte ratio with overweight in children. Methods: A case control study was conducted on 45 obese children aged from 4 years to 18 years who were following in Mansoura University Children’s Hospital out patient clinics with 40 matched control group, during the period from November 2021 till November 2023. Anthropometric measurements assessed and inflammatory markers were withdrawn from each group. Results: A statistically significant difference was detected between the studied groups as regards body mass index (P=0.001). Statistically significant higher mean values fasting glucose, among cases than the control group. A statistically significant positive correlation between Neutrophil/lymphocyte ratio and waist circumference (r=0.455). Conclusion: According to our findings, it can be concluded that overweight is an inflammatory state with increasing inflammatory markers in obese children..